Zinc sulfate inhibits the enterohepatic cycling of unconjugated bilirubin in subjects with Gilbert’s syndrome - Nahum Méndez-Sánchez, MD, PhD; Mariana Martínez; Verónica González; Ernesto Roldán-Valadez, MD; Miguel A Flores, MD; Misael Uribe, MD (Annals of Hepatology, 2002)
We have previously observed that UCB binds to ZnSO4in vitro, and suppresed the biliary bilirubin secretion in the hamster. The aim of this study was designed to investigate whether Zn salts might inhibit the enterohepatic cycling of UCB in subjects with Gilbert´s syndrome. Fifteen patients with Gilbert´s syndrome and 5 normal healthy volunteers were included in this study according to the following criteria: fasting hyperbilirubinemia, no hemolysis, and free of any medication. Patients were randomly assigned to receive acute o chronic treatment. Subjects treated in acute form and normal healthy volunteers were treated with 40 mg of ZnSO4 in a single dose, where as patients treated in chronic form received 100 mg ZnSO4 in a single dose daily for 7 days. The serum UCB levels (mg/dL) decreased from 2.64 ± 1.04 to 2.02 ± 0.87 (p < 0.001) and 1.8 ± 0.36 to 1.48 ± 0.32 (p < 0.005) in subjects treated in acute an chronic form respectively, but not in the control group. Whereas, the serum Zn levels (μg/dL) increased from 96.3 ± 16.8 to 118.8 ± 19. 5, (p < 0.01) and from 117.6 ± 8.5 to 130.7 ± 6.6 (p < 0.03) in subjects treated in acute an chronic form and also in subjects in the control group (98.0 ± 7.3 to 128.0 ± 21.9) p < 0.03. This study showed that acute and chronic oral administration of ZnSO4 decreased serum UCB levels significantly in subjects with Gilbert´s syndrome. Most likely by the inhibition of the “normal” enterohepatic cycling of UCB.